2018
DOI: 10.1002/2017jg004159
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Considered Organic Versus Inorganic Source of Carbon to Lakes for Calculating Net Effect on Landscape C Budgets

Abstract: Lakes and reservoirs transform, emit, and bury carbon that is exported from land and are thus significant components of terrestrial carbon budgets. Their significance is often assessed by integrating these water bodies into terrestrial primary production. However, the transfer of inorganic carbon (IC) is likely a sticking point for these integrations because IC is not part of net ecosystem production. Here we integrated carbon evasion and organic carbon (OC) burial in a lake in the context of inorganic and OC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 68 publications
0
9
0
Order By: Relevance
“…However, the degradation of organic matter is dominant in this area as indicated by the depletion of 13 C in the bottom region (Han et al, 2018;Wang et al, 2019c). DIC generated at the bottom of the reservoir will further promote the photosynthesis of surface water downstream of the reservoir via discharged water (f5, f6), and provide support for the degradation of organic matter (equation 4) at the bottom (Wang et al, 2019b;Lu et al, 2018).…”
Section: Influence Of Hrt and Environmental Factors On Dic Variationmentioning
confidence: 99%
“…However, the degradation of organic matter is dominant in this area as indicated by the depletion of 13 C in the bottom region (Han et al, 2018;Wang et al, 2019c). DIC generated at the bottom of the reservoir will further promote the photosynthesis of surface water downstream of the reservoir via discharged water (f5, f6), and provide support for the degradation of organic matter (equation 4) at the bottom (Wang et al, 2019b;Lu et al, 2018).…”
Section: Influence Of Hrt and Environmental Factors On Dic Variationmentioning
confidence: 99%
“…The results of C/N ratio and d 13 C-POC also confirmed that the main source of POC in sediment was from phytoplankton [12]. Based on an endmembers mixing model, Lu et al [38] reported that endogenous organic carbon formed by photosynthesis contributed 85% to OC in the sediments of the HFR, and the exogenous OC accounted for only 15%. Our study used this ratio of endogenous OC to calculate the valid carbon sink of the HFR and found that the valid carbon sink in the HFR is 4,632 t of carbon per year.…”
Section: Source Analysis Of Carbon Sink In Sedimentsmentioning
confidence: 57%
“…Traditionally, these newly formed OC is thought to be mainly from the rephotosynthetic utilization of DIC formed by the decomposition process of terrestrial organic matter (including POC, DOC) in river courses [37]. Lu et al [38] confirmed in their research on reservoirs in Karst areas that the carbon of newly formed organic matter in reservoirs is largely derived from soil CO 2 , and the photosynthetic absorption process in the reservoir prevented these CO 2 from being released into the atmosphere. Consequently, this part of carbon should be regarded as the valid carbon sink.…”
Section: Source Analysis Of Carbon Sink In Sedimentsmentioning
confidence: 99%
“…Such imbalances can reach a point where lakes are simultaneously in an autotrophic state, yet they emit CO 2 to the atmosphere, as is likely the case in approximately one third of lakes in the boreal region and in the contiguous United States (Bogard & Giorgio, 2016;McDonald et al, 2013). Accounting for the role of calcite precipitation on C dynamics at a local scale is necessary to improve the reliability and predictability of lake models that are currently unable to explain the reported imbalances between metabolism and C fluxes (Lu et al, 2018). (Mendonça et al, 2017) in lakes and reservoirs.…”
Section: Resultsmentioning
confidence: 99%